Preparation of chitosan / bentonite loaded copper material and application of chitosan / bentonite loaded copper material in catalysis of boron addition reaction

By using chitosan/bentonite-supported copper catalyst, the problems of high cost and environmental pollution in the preparation of organoboron compounds in the existing technology have been solved, realizing a low-cost and high-efficiency boron addition reaction. The catalyst is easy to recycle and reuse, and the yield is as high as 99%.

CN120961220APending Publication Date: 2025-11-18HUBEI ENG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510977993.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-16
Publication Date
2025-11-18

AI Technical Summary

Technical Problem

Existing methods for preparing organoboron compounds are costly, environmentally unfriendly, and require expensive transition metals and strong base additives, making it difficult to achieve efficient and low-cost boron addition reactions.

Method used

A copper catalyst supported on chitosan/bentonite was developed, achieving high yields of boron compounds under mild conditions through a simple preparation method. The combination of chitosan and bentonite to support copper forms a stable cross-linked network, improving the stability and activity of the catalyst.

Benefits of technology

It achieves a low-cost, environmentally friendly catalytic boron addition reaction, the catalyst is easy to recover and reuse, the yield is as high as 99%, the operation is simple, and it meets the requirements of green and sustainable development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120961220A_ABST
    Figure CN120961220A_ABST
Patent Text Reader

Abstract

The invention discloses preparation of a chitosan / bentonite loaded copper material and application of the chitosan / bentonite loaded copper material in catalysis of boron addition reaction, and relates to the field of boron compound synthesis. According to the application, an alpha, beta-unsaturated compound and bis (pinacolato) diboron are used as raw materials, a chitosan / bentonite loaded copper material is used as a catalyst, reaction is performed at room temperature, and the organic boron compound can be obtained through separation and purification. The raw materials of the catalyst are cheap and easy to obtain, the catalyst is simple to prepare, easy to recover and reuse, high yield can be obtained only with low catalyst dosage, and the catalyst has huge industrial practical potential.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the field of boron compound synthesis, in particular to a preparation of chitosan / bentonite supported copper material and its application in catalyzing boron addition reaction. BACKGROUND

[0002] Organoboron compounds are valuable components in organic synthesis, widely used in drug manufacturing and material processing. In the prior art, organoboron compounds are mostly prepared by homogeneous catalysis with expensive and toxic transition metals. Although the activity is high, strong base additives, expensive ligands and transition metals are usually required, which does not meet the requirements of green and sustainable development. It has been concerned to explore practical and convenient methods for preparing organoboron compounds, and it is urgent to develop promising methods to overcome the limitations of traditional preparation. Heterogeneous catalysis is a sustainable alternative to homogeneous methods of organic transformation. This method is low in cost, simplifies the catalyst separation process, and can realize large-scale industrial production. These advantages make heterogeneous catalysis possible in large-scale synthesis of valuable chemicals.

[0003] Chitosan has high efficiency as a support material due to its biodegradability, biocompatibility, non-toxicity and easy availability. It is a natural polymer suitable for constructing heterogeneous catalysts. Bentonite is used as an ion exchanger, adsorbent or catalyst in many industrial fields due to its low cost, environmental compatibility, reusability, simple operation and easy availability. In addition, bentonite provides good support for metal ions and provides good dispersion and excellent adsorption due to its low cost and non-toxicity. There are few reports in the prior art on the preparation of heterogeneous catalysts by loading metals on bentonite and chitosan.

[0004] Therefore, it is necessary to develop a chitosan / bentonite supported copper catalytic material, which is low in cost, environmentally friendly, easy to recycle and reuse, and can realize high yield of boron compounds under mild conditions with low catalyst dosage when applied to catalyze boron addition reaction. SUMMARY

[0005] The purpose of the present application is to solve the problems in the prior art. The present application provides a chitosan / bentonite supported copper catalytic material, which is low in cost, environmentally friendly, easy to recycle and reuse, and can realize high yield of boron compounds under mild conditions with low catalyst dosage when applied to catalyze boron addition reaction.

[0006] The technical scheme of the present application is as follows: A preparation method of chitosan / bentonite supported copper material, comprising: Step (1), quickly adding chitosan into acetic acid solution, stirring at room temperature to obtain system one; Step (2), the bentonite is dispersed in distilled water, and ultrasonic treatment is performed to obtain system two; Step (3), system one obtained in step (1) is slowly added to system two obtained in step (2), and stirring is performed at 40-50°C for 12-24 h to obtain system three; Step (4), system three obtained in step (3) is added dropwise into a basic solution, and chitosan / bentonite gel microspheres are formed and washed with water until neutral; Step (5), the chitosan / bentonite gel microspheres washed with water in step (4), and a glyoxal aqueous solution are added into a methanol system, and stirring is performed under reflux conditions for one day to perform a crosslinking reaction, and after the reaction is completed, the crosslinked material is washed and dried to obtain chitosan / bentonite crosslinked microspheres; Step (6), the chitosan / bentonite crosslinked microspheres obtained in step (5) and CuCl2 are placed in an ethanol system, and continuous reaction is performed at a certain temperature, and after the reaction is completed, filtration, washing and drying are performed to obtain chitosan / bentonite copper-loaded material CS / UN@CU.

[0007] Preferably, in step (1), the concentration of the acetic acid solution is 0.02-0.08 M, and the amount ratio of chitosan to acetic acid solution is 1 g:45-55 mL, and stirring is performed at room temperature for 3-4 h. More preferably, the concentration of the acetic acid solution is 0.05 M, and the amount ratio of chitosan to acetic acid solution is 1 g:50 mL.

[0008] Preferably, in step (2), the amount ratio of bentonite to distilled water is 1 g:70-80 mL, and the ultrasonic treatment time is 40-60 min. In step (1), the mass ratio of chitosan to bentonite in step (2) is 1:0.95-1.05. More preferably, the amount ratio of bentonite to distilled water is 1 g:75 mL, and the mass ratio of chitosan in step (1) to bentonite in step (2) is 1:1.

[0009] Preferably, in step (4), the basic solution is obtained by mixing water, methanol and NaOH, and the amount ratio of water, methanol and NaOH is (38-40) mL:(58-60) mL:(10-12) g. More preferably, the amount ratio of water, methanol and NaOH is 40 mL:60 mL:12 g. The amount of the basic solution is sufficient for gelation.

[0010] Preferably, in step (5), the mass concentration of the glyoxal aqueous solution is 40%, the amount ratio of chitosan to 40% glyoxal aqueous solution is 1 g:(2-3) mL, and the reflux temperature is 48-52°C. More preferably, the amount ratio of chitosan to 40% glyoxal aqueous solution is 1 g:2.5 mL, and the reflux temperature is 50°C.

[0011] Preferably, in step (6), the mass ratio of chitosan in step (1) to CuCl2 in step (6) is 1:0.1-0.2. The reaction temperature in step (6) is 40-50°C, and the reaction time is 3-6 h.

[0012] More preferably, the mass ratio of chitosan to CuCl2 is 1:0.1, the reaction temperature in step (6) is 50°C, and the reaction time is 6 h.

[0013] In the above step (5), the methanol system refers to pure methanol, and methanol is used to provide a reaction environment. Preferably, the amount of methanol is as follows: the volume ratio of 40% glyoxal aqueous solution to methanol is 1:9.5-10.5.

[0014] In the above step (6), the ethanol system refers to pure ethanol, and ethanol is used to provide a reaction environment. Preferably, the amount of ethanol is as follows: the amount ratio of CuCl2 to ethanol is 1g:100-200mL. More preferably, the amount ratio of CuCl2 to ethanol is 1g:150mL.

[0015] The application also provides a chitosan / bentonite supported copper material prepared by any of the above-mentioned preparation methods.

[0016] The application also provides an application of the above chitosan / bentonite supported copper material in catalyzing a boron addition reaction, which comprises the following synthesis steps: The α,β-unsaturated compound, pinacol diboronic acid, and the chitosan / bentonite supported copper material CS / UN@CU are added into a solvent formed by methanol and water, and stirred at room temperature to react. After filtration, extraction, drying, and rotary evaporation, a boron compound crude product is obtained. The boron compound crude product is purified by column chromatography to obtain a pure boron compound product. The structure of the α,β-unsaturated compound is wherein R1 is one of phenyl and p-tolyl; and R2 is one of phenyl, p-tolyl, and p-chlorophenyl.

[0017] Preferably, the amount ratio of the α,β-unsaturated compound, pinacol diboronic acid, and the copper supported by CS / UN@CU is 1:(1.2-2.0):(0.01-0.06); and the reaction condition is stirring at room temperature for 3-12 h. More preferably, the amount ratio of the α,β-unsaturated compound, pinacol diboronic acid, and the copper supported by CS / UN@CU is 1:2:0.02, and stirring is performed at room temperature for 12 h.

[0018] Preferably, the solvent is formed by methanol and water at a volume ratio of 4:1, and the content of the copper supported by CS / UN@CU is 1.0-1.3mmol / g. ​

[0019] Preferably, the precipitate obtained after filtration is washed, dried, and then the recovered chitosan / bentonite supported copper catalytic material CS / UN@CU is obtained for the next recycling.

[0020] The reaction formula of the boron addition reaction is as follows: The beneficial effects of the present application are: 1) In the preparation of CS / UN@CU, the gel microspheres formed in step (4) are easy to swell and break, and at this time the chitosan is only physically adsorbed on the bentonite particles, which is easy to fall off in the subsequent stirring reaction process. Therefore, through the crosslinking in step (5), the aldehyde group of glyoxal reacts with the amino group of chitosan to form a covalent crosslinking network, which improves the stability of the microspheres, and at the same time the crosslinking network can wrap the bentonite, and the -NH2 of chitosan and the -OH of bentonite can also form hydrogen bonds, further enhancing the binding force, and forming a structurally stable chitosan / bentonite crosslinked microsphere.

[0021] 2) In the preparation of CS / UN@CU, step (6) loads CuCl2 on the chitosan / bentonite crosslinked microspheres in an ethanol system, which can better maintain the physical structure of the composite microspheres, protect the chemical stability of the functional polymer, and significantly improve the efficiency of subsequent processing.

[0022] 3) Only chitosan, bentonite, and acetic acid are used to synthesize the catalyst at room temperature, which is simple, fast, low in production cost, easy to operate, and environmentally friendly.

[0023] 4) The catalyst is heterogeneous, easy to recover, and can be recycled, which greatly reduces the industrial economic cost.

[0024] 5) In the present application, the chitosan / bentonite supported copper catalyst and B2(pin)2 first form a copper boron complex in a mixture of methanol and water, then the copper boron complex undergoes conjugate addition with α,β-unsaturated acceptor to generate an organocopper species, and methanol and water protonate the organocopper species to obtain the final product. In the whole process, methanol and water act as proton sources, and the chitosan / bentonite supported copper catalyst promotes the asymmetric conjugate boron addition reaction, thereby obtaining the target boron compound.

[0025] 6) The conversion rate is high during the synthesis of boron compounds, the product is easy to separate, the conditions are mild, the operation is simple, and the yield is as high as 99%. The accompanying drawings, which are included to provide a further understanding of the application and are incorporated in and constitute a part of this application, illustrate embodiments of the application and serve to explain the principles of the application. In the drawings: Figure 1 Figure 1 is an XRD pattern of chitosan / bentonite supported copper in Example 1. Figure 2 FTIR of copper loaded on chitosan / bentonite for example 1; Figure 3 NMR of hydrogen of target product for example 2; Figure 4 NMR of carbon of target product for example 2; Figure 5 NMR of hydrogen of target product for example 3; Figure 6 NMR of carbon of target product for example 3; Figure 7 NMR of hydrogen of target product for example 4; Figure 8 NMR of carbon of target product for example 4. DETAILED DESCRIPTION

[0026] The principles and features of the present application are described below in conjunction with the accompanying drawings, in which the examples are used to explain the present application and are not intended to limit the scope of the present application. The drugs used in the examples are commercially available products unless otherwise specified, and the methods used are conventional methods in the art unless otherwise specified.

[0027] The working principle of the present application is as follows: in the present application, the copper loaded on chitosan / bentonite catalyst and B2(pin)2 first form a copper boron complex in a mixture of methanol and water, then the copper boron complex undergoes conjugate addition with α,β-unsaturated acceptor to generate an organocopper species, methanol and water protonate the organocopper species to obtain the final product. Throughout the process, methanol and water act as proton sources, and the copper loaded on chitosan / bentonite catalyst promotes the asymmetric conjugate boron addition reaction, thereby obtaining the target boron compound.

[0028] Example 1 The copper loaded on chitosan / bentonite catalyst is prepared by the following method: Step (1), 2 g of chitosan (2 g of chitosan contains amino-NH20.0106 mol) is added to 100 mL of 0.05M acetic acid solution, and stirred at room temperature for 4 h to obtain system one; Step (2), 2 g of bentonite is dispersed in 150 mL of distilled water and ultrasonically treated for 60 min to obtain system two; Step (3), system one is slowly added to system two, and stirred at 50°C for 24 h to obtain system three; Step (4), the obtained system three is placed in a syringe, and added dropwise to a basic solution by using the syringe, the basic solution is obtained by mixing water 40 mL, methanol 60 mL, NaOH 12 g, to form chitosan / bentonite gel microspheres, and washed with water until the washing liquid is neutral. Step (5), the chitosan / bentonite gel microspheres washed with water, 5 mL of 40% mass concentration of glyoxal aqueous solution was added into 50 mL of methanol system, and stirred at 50°C under reflux conditions for one day (24h) for crosslinking, after filtration, washed with methanol and dried to obtain chitosan / bentonite crosslinked microspheres; Step (6), chitosan / bentonite microspheres and 0.2 g of CuCl2 were placed in 30 mL of ethanol system, and reacted at 50°C for 6 h, after the reaction was completed, filtered and washed to dry to obtain the corresponding chitosan / bentonite copper-loaded catalytic material CS / UN@CU. The copper content in the catalyst was calculated by ICP test: 1.1394 mmol / g.

[0029] Figure 1 is the XRD graph of chitosan / bentonite copper-loaded material. It can be seen from the graph that the crystal has good crystallinity. The main peak of chitosan in the composite material is located at 2θ = 20.6°, and the main peak of bentonite is located at 26.6°, which proves the successful preparation of chitosan / bentonite copper-loaded material.

[0030] Figure 2 is the FTIR graph of chitosan / bentonite copper-loaded material. In the graph, the characteristic peaks of chitosan are respectively: 3442 cm -1 , 3165 cm -1 O-H and N-H stretching vibration (broad peak, hydrogen bonding); 2859 cm -1 (C-H stretching vibration of methyl and methylene imine); 1643 cm -1 (bending vibration of N-H); 1080 cm -1 , 901 cm -1 (β-glycosidic bond). The characteristic peaks of bentonite are respectively: 3650 cm -1 (AI-OH stretching vibration); 1397 cm -1 , 1112 cm -1 (O-Si-O stretching vibration, 777 cm -1 (A1-O-Si deformation vibration). The above results show that the chitosan / bentonite copper-loaded material is successfully synthesized.

[0031] Example 2 The chitosan / bentonite copper-loaded catalyst prepared in Example 1 was applied to the synthesis of boron compounds reaction with chalcone as substrate, chalcone is α, β-unsaturated compound (R1, R2 are both phenyl), including the following steps: 1) 0.2 mmol chalcone, 0.4 mmol pinacolboronic acid reagent and copper catalyst with a copper loading of 0.004 mmol chitosan / bentonite supported copper catalyst CS / UN@CU were added to 2 mL of solvent with a methanol:water ratio of 4:1 (v:v) and mixed and stirred at room temperature for 12 h; the chemical reaction formula is as follows: 2) After the reaction was completed, the obtained mixed system was centrifuged and filtered. The obtained mixed solution was extracted with ethyl acetate solution, dried with anhydrous Na2SO4 and rotary evaporated to obtain a boronide crude product.

[0032] 3) The obtained boronide crude product was purified by column chromatography to obtain the corresponding organoboron compound. After the obtained precipitate was washed and dried, the recovered chitosan / bentonite supported copper catalyst material CS / UN@CU was obtained and used in the next cycle.

[0033] In this example, the chitosan / bentonite supported copper catalyst material was applied to the boron addition reaction of chalcone, and the yield of the target product (boron-based compound) was 83%.

[0034] The nuclear magnetic hydrogen spectrum and carbon spectrum of the target product are shown in Figures 3-4 , and the data are shown as follows: 1 H NMR (400 MHz, Chloroform- d ) δ 7.91 – 7.86 (m, 2H), 7.46 (d, J = 7.3Hz, 1H), 7.36 (t, J = 7.6 Hz, 4H), 7.22 (d, J = 2.0 Hz, 2H), 7.09 (s, 1H), 3.46(d, J = 10.8 Hz, 1H), 3.34 (dd, J = 24.1, 5.6 Hz, 1H), 2.73 (dd, J = 10.8, 5.0 Hz,1H), 1.13 (d, J = 31.6 Hz, 12H). 13 C NMR (100 MHz, Chloroform- d ) δ 199.7, 142.0, 136.8, 132.9, 128.5,128.4, 128.1, 125.6, 83.4, 47.4, 43.3, 24.6, 24.5. Example 3 The chitosan / bentonite supported copper catalyst prepared in Example 1 was applied to the synthesis of boron compound reaction with (E)-1-phenyl-3-(p-tolyl)prop-2-en-1-one as substrate, (E)-1-phenyl-3-(p-tolyl)prop-2-en-1-one is an α, β-unsaturated compound (R1 is phenyl, R2 is p-tolyl), including the following steps: 1) 0.2 mmol (E)-1-phenyl-3-(p-tolyl)prop-2-en-1-one, 0.4 mmol pinacolboronic acid reagent and chitosan / bentonite supported copper catalyst CS / UN@CU with copper loading of 0.004 mmol were added to 2 mL of methanol: water = 4:1 (v:v) solvent, and stirred at room temperature for 12 h; the chemical reaction formula is as follows: 2) After the reaction was completed, the obtained mixed system was centrifuged and filtered. The obtained mixture was extracted with ethyl acetate solution, dried with anhydrous Na2SO4 and rotary evaporated to obtain the boron compound crude product.

[0035] 3) The obtained boron compound crude product was purified by column chromatography to obtain the corresponding organic boron compound. After the obtained precipitate was washed and dried, the recovered chitosan / bentonite supported copper catalyst material CS / UN@CU was obtained for the next cycle.

[0036] In this example, the chitosan / bentonite supported copper catalyst material was applied to the boron addition reaction of (E)-1-phenyl-3-(p-tolyl)prop-2-en-1-one, and the yield of the target product (boron-based compound) was 99%.

[0037] The nuclear magnetic hydrogen spectrum and carbon spectrum of the target product are shown in Figures 5-6 , and the data are as follows: 1 H NMR (400 MHz, Chloroform- d ) δ 7.95 – 7.74 (m, 2H), 7.44 (d, J = 7.3Hz, 1H), 7.35 (dd, J = 8.4, 7.0 Hz, 2H), 7.12 (d, J = 8.0 Hz, 2H), 7.01 (d, J = 7.8Hz, 2H), 3.52 – 3.20 (m, 2H), 2.68 (dd, J = 10.8, 5.0 Hz, 1H), 2.23 (s, 3H),1.13 (d,J = 31.3 Hz, 12H). 13 C NMR (100 MHz, Chloroform- d ) δ 199.8, 138.8, 136.9, 135.0, 132.9,128.5, 128.3, 128.1, 83.4, 43.5, 24.6, 24.6, 21.0. Example 4 The chitosan / bentonite supported copper catalyst prepared in Example 1 was applied to the synthesis of boron compound reaction with (E)-3-(4-chlorophenyl)-1-(p-tolyl)prop-2-en-1-one as substrate, (E)-3-(4-chlorophenyl)-1-(p-tolyl)prop-2-en-1-one is α, β-unsaturated compound (R1 is p-tolyl, R2 is p-chlorophenyl), including the following steps: 1) 0.2 mmol (E)-3-(4-chlorophenyl)-1-(p-tolyl)prop-2-en-1-one, 0.4 mmol pinacolboronic acid reagent and copper loading 0.004 mmol chitosan / bentonite supported copper catalyst CS / UN@CU were added to 2 mL of methanol: water = 4:1 (v:v) solvent, and stirred at room temperature for 12 h; the chemical reaction formula is as follows: 2) After the reaction, the obtained mixed system was centrifuged and filtered. The obtained mixture was extracted with ethyl acetate solution, dried with anhydrous Na2SO4 and rotary evaporated to obtain boron compound crude product.

[0038] 3) The obtained boron compound crude product was purified by column chromatography to obtain the corresponding organic boron compound. The recovered chitosan / bentonite supported copper catalyst material CS / UN@CU was obtained by washing and drying the precipitate obtained by filtration, which was used for the next cycle.

[0039] In this example, the chitosan / bentonite supported copper catalyst was applied to the boron addition reaction of (E)-3-(4-chlorophenyl)-1-(p-tolyl)prop-2-en-1-one, and the yield of the target product (boron-based compound) was 91%.

[0040] The nuclear magnetic hydrogen spectrum and carbon spectrum of the target product are shown in Figures 7-8 The data are as follows: 1 H NMR (400 MHz, Chloroform-d) δ 7.78 (d, J= 8.2 Hz, 2H), 7.18 – 7.14(m, 6H), 3.35 (dd, J = 21.8, 7.9 Hz, 2H), 2.69 (dd, J = 10.3, 5.4 Hz, 1H), 2.32(s, 3H), 1.13 (d, J = 27.9 Hz, 12H). 13 C NMR (100 MHz, Chloroform- d ) δ 199.0, 143.8, 140.7, 134.2, 131.3,129.2, 128.5, 128.2, 83.5, 42.8, 29.7, 24.6, 24.5, 21.6. The above description is only the preferred embodiment of the present application, and does not limit the present application in any form; any person skilled in the art can easily implement the present application according to the drawings and the above description; however, any equivalent changes, modifications and evolutions made by those skilled in the art within the scope of the technical solutions of the present application, using the disclosed technical content, are equivalent embodiments of the present application; at the same time, any equivalent changes, modifications and evolutions made according to the essence of the present application to the above embodiments are still within the protection scope of the technical solutions of the present application.

Claims

1. A method for preparing a chitosan / bentonite-supported copper material, characterized in that, include: Step (1): Quickly add chitosan to the acetic acid solution and stir at room temperature to obtain system one; Step (2): Disperse bentonite in distilled water and sonicate to obtain system two; Step (3): Slowly add System 1 obtained in Step (1) to System 2 obtained in Step (2), and stir at 40~50℃ for 12~24 h to obtain System 3; Step (4): Add three drops of the system obtained in step (3) to an alkaline solution to form chitosan / bentonite gel microspheres and wash with water until neutral; Step (5): Add the chitosan / bentonite gel microspheres washed in step (4) and glyoxal aqueous solution to the methanol system, and stir under reflux for one day to carry out the cross-linking reaction. After the reaction is completed, wash and dry the cross-linked material to obtain chitosan / bentonite cross-linked microspheres. Step (6): Place the chitosan / bentonite cross-linked microspheres obtained in step (5) and CuCl2 in an ethanol system and continue to react at a certain temperature. After the reaction is completed, filter, wash and dry to obtain chitosan / bentonite-supported copper material CS / UN@CU.

2. The method for preparing chitosan / bentonite-supported copper material as described in claim 1, characterized in that, In step (1), the concentration of the acetic acid solution is 0.02~0.08 M, the ratio of chitosan to acetic acid solution is 1g:45~55 mL, and the mixture is stirred at room temperature for 3~4 h.

3. The method for preparing chitosan / bentonite-supported copper material as described in claim 1, characterized in that, In step (2), the ratio of bentonite to distilled water is 1g:70~80 mL, and the ultrasonic treatment time is 40~60 min; The mass ratio of chitosan in step (1) to bentonite in step (2) is 1:0.95~1.

05.

4. The method for preparing chitosan / bentonite-supported copper material as described in claim 1, characterized in that, In step (4), the alkaline solution is obtained by mixing water, methanol and NaOH, and the ratio of water, methanol and NaOH is (38~40) mL:(58~60) mL:(10~12) g.

5. The method for preparing chitosan / bentonite-supported copper material as described in claim 1, characterized in that, In step (5), the mass concentration of the glyoxal aqueous solution is 40%, and the ratio of chitosan to 40% glyoxal aqueous solution in step (1) is 1g:(2~3)mL, with a reflux temperature of 48~52℃.

6. The method for preparing chitosan / bentonite-supported copper material as described in claim 1, characterized in that, The mass ratio of chitosan in step (1) to CuCl2 in step (6) is 1:0.1~0.2; In step (6), the reaction temperature is 40~50℃ and the reaction time is 3~6 h.

7. A chitosan / bentonite-supported copper material, characterized in that, It is prepared by the method for preparing chitosan / bentonite-supported copper material as described in any one of claims 1 to 6.

8. The application of the chitosan / bentonite-supported copper material as described in claim 7 in a catalytic boron addition reaction, characterized in that, The synthesis steps include the following: α,β-unsaturated compounds, pinacol diboronate, and chitosan / bentonite-supported copper material CS / UN@CU were added to a solvent formed by methanol and water and stirred at room temperature. After filtration, extraction, drying, and rotary evaporation, crude boride products were obtained. The crude boride products were purified by column chromatography to obtain pure boron compound products. The structural formula of the α,β-unsaturated compound is as follows: , R1 is one of phenyl or p-tolyl; R2 is one of phenyl, p-tolyl, or p-chlorophenyl.

9. The application of the chitosan / bentonite-supported copper material as described in claim 8 in the catalytic boron addition reaction, characterized in that, The molar ratio of α,β-unsaturated compound, pinacol diboronate, and copper loaded in CS / UN@CU is 1:(1.2~2.0):(0.01~0.06); the reaction conditions are stirring at room temperature for 3~12 h.

10. The application of the chitosan / bentonite-supported copper material as described in claim 8 in the catalytic boron addition reaction, characterized in that, Methanol and water were mixed in a volume ratio of 4:1 to form a solvent, and the copper content loaded in CS / UN@CU was 1.0~1.3 mmol / g.